Outcome predictors of severe and very severe pneumonia in children between 2 and 59 months of age admitted in a tertiary care hospital - Ansari, MD Ehtesham; Kumar, Ajay; Aggarwal, K C; Meena, K R; Kamal, Murtaza (Indian Journal of Child Health, 2016)
Objective: The objective of this study was to determine the factors associated with outcome (morbidity and mortality) in children aged 2-59 months with severe and very severe pneumonia. Materials and Methods: This is a hospital-based, prospective, observational study conducted in the pediatric department of a tertiary care hospital. Totally 300 children of either sex between 2 and 59 months of age with the WHO-defined severe pneumonia and very severe pneumonia were enrolled in the study. Associations of outcomes and various clinical symptoms were assessed using Chi-square test first and then through logistic regression models. Results: In our study, 86 (28.7%) children stayed in hospital more than 5 days, 113 (37.7%) needed change in antibiotics, 24 (8%) developed complications (5% effusion and 3% pneumothorax), and 31 (10.3%) expired. Multivariate analysis showed that younger age at presentation, household pollution (cooking fuel other than liquefied petroleum gas), and children who did not receive exclusive breastfeeding were prone to develop more severe pneumonia. Head nodding and cyanosis were independent factors significantly associated with mortality on multiple logistic regression. Radiologically proven pneumonia cases required change in antibiotics more frequently and stayed for longer duration in hospital as compared to clinical pneumonia cases. Conclusions: Children with signs of severe respiratory distress such as head nodding, cyanosis and altered sensorium, anemia, decreased or increased total leukocyte count, and hypoxemia have greater risk of mortality. Children with risk factors including overcrowding, indoor air pollution, lack of exclusive breastfeeding and proper immunization, and abnormal chest radiograph are less likely to respond to the first-line antibiotics; therefore, they may be treated aggressively with the second-line antibiotics from the beginning so that their hospital stay may be reduced.